2022
DOI: 10.1186/s12911-022-01914-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a computerized decision support system to review pharmacotherapy treatment: scheduling guidelines

Abstract: Background The review of pharmacotherapy can be conceptualized as a service in which the drugs used by the patient are reviewed to control the risks as well as to improve the results of the drug therapy, detecting, solving, and preventing issues associated with the drug, readjusting the doses and times (schedule) so that the treatment is not incompatible or in duplicity. Methods The aim of the study was to validate an intelligent information system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A study carried out by Zapelini and collaborators (2021) compared the result of the manual pharmaceutical evaluation with the evaluation of a computerized system developed by the researcher and, also, the computerized system was superior to the manual evaluation of the pharmacist 14 . Another study conducted by Levivien et al (2022) also found a better performance of the hybrid system when compared to manual pharmaceutical practice, in this case, the developed system was able to identify a greater number of problems related to medications 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out by Zapelini and collaborators (2021) compared the result of the manual pharmaceutical evaluation with the evaluation of a computerized system developed by the researcher and, also, the computerized system was superior to the manual evaluation of the pharmacist 14 . Another study conducted by Levivien et al (2022) also found a better performance of the hybrid system when compared to manual pharmaceutical practice, in this case, the developed system was able to identify a greater number of problems related to medications 15 .…”
Section: Discussionmentioning
confidence: 99%